A Comparative Study of Lemongrass (Cymbopogon Citratus) Essential Oil Extracted by Microwave-Assisted Hydrodistillation (MAHD) and Conventional Hydrodistillation (HD) Method - Ranitha, Mathialagan; Nour, A. H.; Ahmad Ziad, Sulaiman; Azhari, H. Nour; Thana, Raj S. (IACSIT Press, 2014)
The demand of essential oil in current industry has increased due to its bioactive compound that shows various therapeutic effects. Microwave-assisted hydrodistillation (MAHD) is an advanced hydrodistillation (HD) technique, in which a microwave oven is used as the heating source. MAHD extraction of essential oil from Lemongrass (Cymbopogon Citratus) was studied. The effect of different parameters, such as water to plant material ratio (6:1, 8:1,10:1), microwave power (200 W,250W) and extraction time (30min,60min, 90min,120min) on the extraction yield and its major constituents were investigated and the results were compared with those of conventional HD. These essential oils were further analyzed by gas chromatography/mass spectrometric (GC-MS) to evaluate the effect of extraction method on the content of its main constituents which were neral, geranial and myrcene and some minor compounds such as linalool, geranic acid and citronellol. The optimum parameters were found at water to plant material ratio of 8:1, microwave power of 250W and 90 minutes of extraction and the yield obtained under this condition was 1.46%. GC-MS analysis has proved that the use of microwave irradiation did not adversely influence the composition of essential oils as the main constituents found through both methods were almost similar in term of quality and quantity. The results obtained indicate that MAHD method provided a good alternative for the extraction of essential oil from Lemongrass (Cymbopogon Citratus)